Analysis and Explanation of the Teaching Characteristics of Professor Motahhari as a Model Teacher Aligned with the Fundamental Reform Document of Education - همتی Hemmati (پژوهش در آموزش معارف و تربیت اسلامی)
Professor Morteza Motahhari is one of the most influential cultural figures of the contemporary era. Exploring the dimensions of his teaching persona, research methodology, and conduct can outline aspects of an ideal teacher model for the Islamic educationsystem. This descriptive-analytical study draws on memoirs from his family, students,and colleagues, as well as his written works. The Islamic educational system and the Fundamental Reform Document emphasize the cultivation of guiding and impactful teachers with holistic personal development. Achieving this goal requires focused attention on teachers’ spiritual and professional growth, necessitating practical role models. Professor Motahhari’s personality and works demonstrate his suitability as a model. By analyzing various dimensions of his character, salient points for teacher training can be practically applied. His ethical traits—such as sincerity, adherence to religious principles, discipline, patience, kindness, and open-mindedness—combined with profound knowledge, audience-tailored content delivery, and engaging teaching techniques define his educational ethos. In research, his success stemmed from depth, coherence, intellectual freedom, principled directionality, and problem-centricity, which underpin the enduring relevance of his works.